Co-substituted CuO–ZrO2–Nb2O5 composite ceramics with low-temperature sintering and low-loss for high-performance patch antenna. Issue 13 (1st July 2022) - Li, Fuyu; Liu, Xinyan; Li, Yuanxun; Tang, Tingting; Liao, Yulong; Lu, Yongcheng; Peng, Rui; Zhang, Qin; Wu, Xiaohui; Wen, Qiye
Abstract: In the field of microwave dielectric ceramics for patch antennas, it has always been a thorny issue to simultaneously satisfy high dielectric constant, low sintering temperature and low dielectric loss. Here, a CCZN ( x  = 0.04) composite ceramic with excellent microwave dielectric properties was developed. It can be found that an appropriate amount of Co 2+ substitution can enhance the compactness, increase the dielectric constant ( ε r ), reduce the dielectric loss (tan δ ) and enhance the temperature coefficient (τ f ). The composite ceramic with excellent dielectric properties ( ε r  = 22.6, Q ×  f  = 37, 624 GHz, τ f  = −64.9 ppm/°C) shows good sintering compatibility with Ag. Based on this composite ceramic, a high-performance patch antenna was designed for Beidou satellite navigation system (BDS). It presents a small size of 30 × 30*3.8 mm 3 and excellent radiation performance (return loss = −32.9 dB, VSWR = 1.047, impedance bandwidth = 60.6 MHz, radiation efficiency = 94.6% and realized gain = 7.704 dB). This work promotes the application of microwave dielectric ceramics in the field of patch antennas.